2018
DOI: 10.21449/ijate.444882
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Attitudes towards Asylum Seekers and Compassion Levels of University Students

Abstract: The aim of this study is to adapt the attitude scale towards asylum seekers and refugees to Turkish culture and to examine the relation of university students' attitudes towards asylum seekers to certain personality traits. The study was conducted with the participation of 340 university students. The attitude scales for both asylum seekers and refugees were adapted to Turkish culture and validity and reliability studies were conducted in the study. Findings have shown that they provide the necessary condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
(15 reference statements)
0
2
0
1
Order By: Relevance
“…Furthermore, theology students show a more positive attitude than students in other faculties. However, there was no gender difference in attitudes towards refugees (Yelpaze and Güler 2018). Based on the literature, the following hypothesis was established.…”
Section: Religiosity Socioeconomic Status and Social Distance Towards Refugeesmentioning
confidence: 99%
“…Furthermore, theology students show a more positive attitude than students in other faculties. However, there was no gender difference in attitudes towards refugees (Yelpaze and Güler 2018). Based on the literature, the following hypothesis was established.…”
Section: Religiosity Socioeconomic Status and Social Distance Towards Refugeesmentioning
confidence: 99%
“…Öğretmenlerin Mülteci ve Suriyeli öğrencilere yönelik algılarının belirlendiği çalışmalara örnek olarak (Aykırı, 2017;Demirtaş & Mentiş Taş, 2019;Keskin, vd., 2019;Çetin, 2021;Özdoğru, vd., 2021;Sağlam & İlksen Kanbur, 2017;İlksen Kanbur, 2017;Yurdakul & Tok, 2018;Köse, vd., 2019;Tezcan, 2019;Dolapcı, 2019;Kardeş & Akman, 2018) gösterilebilir. Öğretmen adayları ve öğrencilerin Mülteci ve Suriyeli öğrencilere yönelik algılarının belirlendiği çalışmalara örnek olarak ise (Kara, vd., 2016;Sarıtaş, vd., 2016;Durmuş & Baş, 2016;Uzun & Özcan, 2017;Yelpaze & Güler, 2018;Taze & Aktın, 2018;Torun & Demirtaş, 2018;Eminoğlu & Eminoğlu, 2020;Burak & Amaç, 2021) çalışmaları örnek olarak gösterilebilir. Bu çalışmaların; öğretmenler, öğretmen adayları, üniversite öğrencileri ve toplumun farklı kesimlerinden insanların sığınmacı öğrencilere yönelik algı, tutum ve görüşlerinin belirlenmesine yönelik gerçekleştirildiği görülmektedir.…”
Section: Journal Of Bayburtunclassified
“…As a result of the data obtained from the research, it was found that Turkish students' metaphors for the concept of "refugee" were generally positive. When the literature is examined, it has been determined that in the studies conducted with teacher candidates (Yelpaze &Güler, 2018;Demirtaş & Mentiş Taş, 2019;Burak &…”
Section: Afadmentioning
confidence: 99%